Evaluating Factors Related to the Incidence and Severity of Dyspnea in Patients with Human Immunodeficiency Virus (HIV) - Sari, Dewi Purnama; Fatma, Endah Panca Lidya; Putri, Irenne Sekar; Yuliatun, Laily; Dewi, Elvira Sari; Arifin, Yusuf; Japar, Salimah (Journal of Nursing Science Update (JNSU), 2025)
Shortness of breath, known as dyspnea, is a symptom that affects 40 to 70% of patients with HIV/AIDS during their hospital stays. Nonetheless, the prevalence and severity of dyspnea among individuals attending outpatient clinics remain inadequately understood. Evaluating dyspnea in the outpatient care setting is essential for preventing further complications and enhancing the quality of life for these patients. This study aims to assess the factors associated with the incidence and severity of dyspnea in individuals diagnosed with HIV in an outpatient context. Additionally, it examines the demographic characteristics of the study population. A cross-sectional observational study was conducted across 68 HIV outpatients. The incidence and severity of dyspnea were evaluated utilizing the Modified Borg Scale (MBS), and bivariate analyses were conducted. The results showed that among 64 individuals (94.1%), 64 exhibited dyspnea. The severity of dyspnea was categorized as follows: no breathlessness (4; 5.9%), very slight (8; 11.8%), very mild (15; 22.1%), mild (10; 14.7%), moderate (11; 16.2%), somewhat severe (7; 10.3%), severe (11; 16.2%), and very severe (2; 2.9%). Statistical analysis revealed no significant association between demographic factors and the incidence of dyspnea (p > 0.05), nor was there a correlation between demographic characteristics and the severity of dyspnea (p > 0.05). In conclusion, the Modified Borg Scale, which incorporates the 6-minute walking test as an assessment tool, can objectively identify and monitor the risk for more severe respiratory complications, even among patients without a prior diagnosis of pulmonary comorbidities.